Negative Traits of Lady of The Green Kirtle as Antagonist in C.S. Lewis’ The Silver Chair - Iswari, Nyoman Astari Pradnya; Suwastini, Ni Komang Arie; Agustini, I Dewa Ayu Eka; Artini, Ni Nyoman (SPHOTA: Jurnal Linguistik dan Sastra, 2025)
An abstract should accompany each manuscript; it should be completely self-consistent (i.e., In children’s literature, protagonists are often highlighted as role models, while antagonists are frequently overlooked, despite their crucial role in creating conflict and shaping the plot. Thus, this study explores the characterization of the Lady of the Green Kirtle, the main antagonist in The Silver Chair by C.S. Lewis. An interactive, qualitative method, as described by Miles, Huberman, and Saldana, was employed in this research. As the main instrument, close reading of the novel was employed to identify and analyze specific subsequences containing the antagonist’s behaviors. The findings reveal that the Lady of the Green Kirtle is characterized by four main traits: manipulative, dominant, cruel, and dangerous. She employed her magic, lies, and violence to manipulate others and achieve her goals. Her presence greatly influences the direction of the plot and the challenges faced by the protagonists. This study demonstrates that examining antagonists can enhance our understanding of character roles in literature, particularly in children's stories.